2019
DOI: 10.1186/s12862-019-1486-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at MHC class II loci influences both olfactory signals and scent discrimination in ring-tailed lemurs

Abstract: Background Diversity at the Major Histocompatibility Complex (MHC) is critical to health and fitness, such that MHC genotype may predict an individual’s quality or compatibility as a competitor, ally, or mate. Moreover, because MHC products can influence the components of bodily secretions, an individual’s body odors may signal its MHC composition and influence partner identification or mate choice. Here, we investigated MHC-based signaling and recipient sensitivity by testing for odor-gene covari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 119 publications
2
15
1
Order By: Relevance
“…In addition to only finding support for gene–odour covariance in certain dyads of individuals, the effect sizes associated with our positive findings were small. Both of these results are consistent with other studies from mammals and birds, which found similar effect sizes and often only detected relationships in certain dyads [26,33,34,62]. The diverse array of factors that affect chemical profiles may explain these findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to only finding support for gene–odour covariance in certain dyads of individuals, the effect sizes associated with our positive findings were small. Both of these results are consistent with other studies from mammals and birds, which found similar effect sizes and often only detected relationships in certain dyads [26,33,34,62]. The diverse array of factors that affect chemical profiles may explain these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Vertebrate chemical profiles change seasonally and may only reflect genetic markers during the breeding season [26,66,67]. The absence of genetic information in chemical profiles during the non-breeding season might be explained by energetic costs associated with producing chemical secretions [67,68], although there is currently limited support for this idea in birds [69].…”
Section: Discussionmentioning
confidence: 99%
“…The MHC marks the scent of urine (both in mice and in humans: Eggert et al 1999) and is quite likely to affect the odor of one's breath, sweat, and genitals as well (Wobst 1999;Aksenov et al 2012;Grogan 2019). It can also alter the menagerie of microbes individuals carry around (Khan et al 2019), and thus the aromatic gases such microbes give off (Rudden et al 2020).…”
Section: Follow Your Nosementioning
confidence: 99%
“…Genotyping the MHC-DRB in a large number of wild and captive lemurs showed that captive animals have reduced allelic diversity [174]. Nevertheless, their allelic diversity relates significantly to the chemical richness of their genital signals and to the responsiveness of conspecifics encountering their scents for the first time [104]. For example, males that have the most MHC-DRB supertypes also have the greatest chemical richness in their genital secretions-attributes that are detectable by female recipients, who associate most often with the scent of MHC-DRB dissimilar males.…”
Section: (C) Focal Studies Of Glandular Secretions In Ring-tailed Lemursmentioning
confidence: 99%
“…They also advertise pairwise kinship or MHC-DRB similarity. Such odour-gene relationships in both sexes facilitate prioritization of agonistic or nepotistic interactions, as well as compatible mate attraction and inbreeding avoidance to increase the immunocompetence of offspring [52,53,[102][103][104]-findings that are functionally relevant to humans and other primates [150,[175][176][177].…”
Section: (C) Focal Studies Of Glandular Secretions In Ring-tailed Lemursmentioning
confidence: 99%